2005
DOI: 10.1191/0269215505cr830oa
|View full text |Cite
|
Sign up to set email alerts
|

Effects of home training and additional physical therapy on recovery after acute unilateral vestibular loss- a randomized study

Abstract: No significant differences in outcome regarding balance function or perceived symptoms were found between home training with or without additional physical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 21 publications
1
62
0
Order By: Relevance
“…It also showed that these benefits were long-term and measurable 6 months later. These results agree with other well-controlled studies emerging in the literature Badke et al, 2005;Kammerlind et al, 2005;Hansson et al, 2004;Murray et al, 2001;Szturm et al, 1994;Horak et al, 1992].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It also showed that these benefits were long-term and measurable 6 months later. These results agree with other well-controlled studies emerging in the literature Badke et al, 2005;Kammerlind et al, 2005;Hansson et al, 2004;Murray et al, 2001;Szturm et al, 1994;Horak et al, 1992].…”
Section: Discussionsupporting
confidence: 83%
“…A recent retro-spective study indicated significant improvements in dynamic posturography performance and self-rated questionnaires (Dizziness Handicap Inventory) after patients had performed an individualised vestibular rehabilitation programme consisting of a weekly supervised session and a home exercise programme [Badke et al, 2005]. Another recent study showed that regular physiotherapy sessions in addition to the patient completing the home exercise programme interestingly did not significantly improve the outcomes [Kammerlind et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…In that condition, vestibular rehabilitation therapy has been shown in a randomized controlled study to improve vestibulospinal function compared to those patients who did not receive therapy following an episode of neuritis [Strupp et al, 1998]. Rehabilitation therapy has also been shown to be effective during the acute phase following sudden vestibular loss [Hillier and McDonnell, 2011;Kammerlind et al, 2005;Teggi et al, 2009;Venosa and Bittar, 2007], and even in cases where the baseline vestibular function is fluctuating, as might be expected in an acutely injured ear whose native function may recover somewhat such as following implantation [Gottshall et al, 2010].…”
Section: Mitigation Of Imbalancementioning
confidence: 99%
“…We [6] have previously performed a randomized controlled trial to evaluate the effects of home training with or without additional physical therapy after acute unilateral vestibular loss. No significant differences between training groups were detected at any of the follow-ups.…”
Section: Introductionmentioning
confidence: 99%